2020
DOI: 10.1002/acr.23838
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Symptom Duration and Patient‐Reported Outcomes Before and After Hip Replacement Surgery

Abstract: Objective Patients experience discomfort and compromised quality of life while waiting for hip replacement. Symptom duration may affect quality of life attained following surgery. We undertook this study to investigate the impact of symptom duration on patient‐reported postsurgical outcomes from hip replacement surgery. Methods National observational data collected before and after hip replacement surgery in England between 2009 and 2016 were used to investigate determinants of symptom duration prior to surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, freed up hospital resources through an expansion of community care activity enables other individuals in need of health care to use hospital services, which may result in a reduction in competing demands for the same hospital bed. This could lead to a potential spill over effect of reduction in waiting times for other patients and may be observed in reduction of symptom duration and benefit of surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, freed up hospital resources through an expansion of community care activity enables other individuals in need of health care to use hospital services, which may result in a reduction in competing demands for the same hospital bed. This could lead to a potential spill over effect of reduction in waiting times for other patients and may be observed in reduction of symptom duration and benefit of surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hip replacement can effectively relieve the joint pain, correct the deformity and recover and improve the joint motor function of patients, thus it is the most effective surgical intervention for elderly patients with hip diseases [ 1 , 2 ]. According to statistics, the incidence rate of postoperative cognitive dysfunction in elderly surgical patients is as high as 38% [ 3 ], posing a serious threat to the surgical effects and prognosis of patients.…”
mentioning
confidence: 99%
“…Previous studies have reported that this may be due to the lack of clarity of the question that was used to elicit information about symptom duration [29]. Nevertheless, increasing symptom duration has recently been reported to be a significant predictor of poorer outcome after surgery [30].…”
Section: Discussionmentioning
confidence: 99%